Fernando Leo Bueno - CO₂ Gasification of Black Liquor Char under isothermal and dynamic conditions (Jornada de Jóvenes Investigadores del I3A, 2025)
CO₂ Gasification of Black Liquor Char under isothermal and dynamic conditions